2023
DOI: 10.1002/adfm.202213401
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized DNA Nanomaterials Targeting Toll‐Like Receptor 4 Prevent Bisphosphonate‐Related Osteonecrosis of the Jaw via Regulating Mitochondrial Homeostasis in Macrophages

Abstract: Imbalance of macrophage polarization characterized by an increase in the percentage of pro-inflammatory M1 macrophages and a decrease in anti-inflammatory M2 macrophages is considered a critical pathogenic mechanism of bisphosphonate-related osteonecrosis of the jaws (BRONJ).Because high levels of Toll-like receptor 4 (TLR4) mediates mitochondrial dyshomeostasis in Zoledronic Acid (ZA)-treated M1 macrophages, tetrahedral DNA nanomaterial (TDN)-modified with TLR4-siRNA on each vertex (TDN-TLR4-4siR) with excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…283 Given that macrophages are activated and amplified in RA, Jain et al 285 studied the effectiveness of nonviral gene transfection strategies to repolarize macrophages from M1 to M2 phenotypes to treat RA. Anti-inflammatory cytokines, such as IL-10, encoding plasmid DNA, were successfully 284,[286][287][288][289] encapsulated by noncondensed alginate-based nanoparticles, the surfaces of which were modified with prophagocytic peptides to achieve active macrophage targeting. Therapy significantly reduced the expression of the proinflammatory cytokines TNF-α, IL-1β, and IL-6 in systemic and joint tissues and arrested the progression of inflammation and joint damage.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…283 Given that macrophages are activated and amplified in RA, Jain et al 285 studied the effectiveness of nonviral gene transfection strategies to repolarize macrophages from M1 to M2 phenotypes to treat RA. Anti-inflammatory cytokines, such as IL-10, encoding plasmid DNA, were successfully 284,[286][287][288][289] encapsulated by noncondensed alginate-based nanoparticles, the surfaces of which were modified with prophagocytic peptides to achieve active macrophage targeting. Therapy significantly reduced the expression of the proinflammatory cytokines TNF-α, IL-1β, and IL-6 in systemic and joint tissues and arrested the progression of inflammation and joint damage.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Downstream HO-1 and SOD2 are also important strands in the antioxidant response. 45,46 Therefore, the expression of Nrf2-associated signaling pathway proteins and genes was examined to verify that Cur-TFNAS can mitigate radiation-induced oxidative stress damage to HOK cells by regulating the Nrf2 signaling pathway. Fluorescence real-time PCR tests revealed that the Nrf2, HO-1, and SOD2 genes were considerably suppressed by radiation (Fig.…”
Section: Cur-tfnas Attenuates Ir-induced Ros Generation By Regulating...mentioning
confidence: 99%
“…In recent years, nucleic acid aptamer-guided drug conjugates (ApDCs) have attracted interest for their extensive targeting features and cost-effectiveness. The nucleic acid aptamers are DNA or RNA with unique sequences and conformations to specifically bind with target molecules, such as small molecules, peptides, and protein. , Aptamers can be easily designed, reproducibly manufactured, and diversely modified for various biological applications. , However, the reported ApDCs were limited with short half-time (within ∼1 h) and low drug-carrier ability (the drug/carrier ratio is limited to 1:1). , Therefore, carrying a sufficient drug dose of ApDCs remains a key question to be addressed. In our previous work, we have demonstrated that the DNA or RNA aptamers could be modified onto tetrahedral framework nucleic acid (tFNA). , The tFNA consists of four single-stranded DNAs (ssDNAs), and the anti-HER2 aptamer (HApt) can be modified onto the end of ssDNA to form the HApt-embedded DNA tetrahedron (HApt-tFNA) . Previous studies have demonstrated the excellent affinity of HApt-tFNA to HER2-positive breast cancer cells. , Therefore, if the cytotoxic drugs were conjugated onto the ssDNAs of HApt-tFNA, new ApDCs would be created with multiplied cargos that could largely enhance antitumor effects.…”
Section: Introductionmentioning
confidence: 99%